Procrastination: The Productivity Killer - Athanasakos, Alvertos; Papadopoulos, Paris; Xenos, Orfeas; Tzelepis, Alexandros (Open Schools Journal for Open Science, 2025)
Procrastination is a prevalent issue that affects individuals of all ages, often leading to decreased productivity, increased stress, and impaired well-being. This paper examines the different types, causes, consequences, and methods to overcome procrastination, aiming to provide students with practical solutions for improvement.